COMPARSION BETWEEN PPO FROM PLANT SOURCES AND DIFFER-ENT CHEMICALS IN TATTOO DYES DECOLORIZATION - Al-Sa'ady, A. J. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to measure the decolorization of tattoo dyes by different chemicals and polyphenol oxidases from several plant sources. The tattoo inks removal market has burgeoned over the years, due to increased spread of tattooed persons about the world. Laser and surgery are presently the gold standards for removing of the tattoo. However, both of them have blemishes. Consequently, lots of persons were preferring easier, faster and cheaper procedures for tattoo remove. In this study polyphenol oxidases enzyme from many plant sources and different chemicals were used for decolorization of tattoo dyes in vitro. The polyphenol oxidase enzyme was used for removing of tattoo dyes (brown and blue) in order to demonstrate their potential in the treatment and decolorization of the tattoo, which is hazardous when removing by laser. The results show that 89 and 82 % of the brown and blue tattoo dyes respectively, were removed after 24 hours by enzyme extracted from Malva parviflora leaves, whereas the decolorization efficiency of polyphenol oxidase from other plant sources given less than 16% of the same dyes. The results for tattoo dyes decolorization by different chemicals revealed that Bimethylbenzylamine was the best chemical used with decolorization ratio 36 and 38 % for brown and blue tattoo dye, respectively.